The Relationship between Delegation of Medical Personnel Authority to Nurses and Nurse Job Satisfaction - Tunny, Hasna; Achmad, Irhamdi (Universitas Airlangga, 2024)
Introduction: Nurses, in carrying out their daily duties, deal directly with medical personnel and the patients they handle. There is a demand to provide health services responsibly by applying treatment according to procedures. Collaborative relationships between doctors and nurses are often a complex problem. Nurses work on delegation of authority (delegation, mandate, and other authorities). This act of delegation of authority affects nurse job satisfaction. The purpose of this study was to determine the relationship between the delegation of authority for medical action from doctors to nurses with the job satisfaction of nurses. Methods: A quantitative descriptive design with a cross-sectional approach was applied to this study. The sample size was calculated through appendicitis pre-operative cases and 60 nurses were involved. Data was collected by self-report study and analyzed using the chi-square test. Results: There is a relationship between the delegation of authority and nurse job satisfaction, delegation (0.000), mandate (0.015), and other authorities (0.000). The process of delegation is more on carrying out doctor's orders or instructions written on the patient's status or medical record. Conclusions: There is an appropriate delegation of authority relationship. This is proven by the process of delegating authority; Hospitals did not apply a standard report on delegation. Nurses' job satisfaction was related to service fees that were also shared with doctors. Re-socialize the delegation process, hospitals need to provide delegation standard reports. This strategy might legally support nurses for their independent, collaborative interventions, and nurse's authority as well.